2021
DOI: 10.4314/ahs.v21i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of oxidative stress and antioxidant response with vaso-occlusive crisis in sickle cell anaemia

Abstract: Background: Though sickle cell anaemia (SCA) is known to promote oxidative stress, there is paucity of information on the relationship between oxidative stress and vaso-occlusive crisis (VOC). Objective: This study was undertaken to evaluate the relationship of oxidative stress and antioxidant response with VOC in SCA. Methods: A cross-sectional case-control study was carried out at University of Nigeria Teaching Hospital (UNTH), Itu- ku-Ozalla, Enugu Nigeria involving 116 individuals which include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The importance of the spleen in preventing the development of autoimmune processes has been demonstrated in studies which have documented high autoantibody titres after splenectomy [ 68 ]. Moreover, chronic inflammation [ 28 ] and alloimmunisation by multiple transfusions have also been implicated in the development of autoantibodies, but these have not been fully confirmed in clinical studies [ 27 , 66 , 67 ]). The coexistence of SCD and autoimmune disease is difficult to treat as those receiving steroids, which are used to control the inflammatory response, experience repeated VOC [ 69 , 70 , 71 ].…”
Section: Autoimmunity In Sickle Cell Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…The importance of the spleen in preventing the development of autoimmune processes has been demonstrated in studies which have documented high autoantibody titres after splenectomy [ 68 ]. Moreover, chronic inflammation [ 28 ] and alloimmunisation by multiple transfusions have also been implicated in the development of autoantibodies, but these have not been fully confirmed in clinical studies [ 27 , 66 , 67 ]). The coexistence of SCD and autoimmune disease is difficult to treat as those receiving steroids, which are used to control the inflammatory response, experience repeated VOC [ 69 , 70 , 71 ].…”
Section: Autoimmunity In Sickle Cell Diseasementioning
confidence: 99%
“…Oxidative stress is an important contributor to the pathogenesis of sickle cell anaemia (SCD) and associated complications such as sickling, vaso-occlusion, and ischemia–reperfusion injury [ 2 , 27 , 36 , 75 , 76 ]. Oxidative stress occurs due to an imbalance between the production of reactive oxygen species (ROS) and reactive nitrogen species (RNS) and the ability of antioxidant agents, including enzymes such as superoxide dismutases, catalase, and glutathione peroxidase, to neutralise them [ 28 , 36 , 77 ]. Patients with SCD are frequently exposed to oxidative stress, and studies have found higher levels of ROS in the RBCs of SCD patients compared to healthy controls.…”
Section: The Role Of Oxidative Stress In the Pathogenesis Of Sickle C...mentioning
confidence: 99%
See 3 more Smart Citations